Analytical Hierarchy Process (AHP) in Decision-Making: A Bibliometric Study - Desvita Putri Maharani; Syahfiah Syahfiah; Wiola Wasa Pebrina Herda; Jelita Jelita; Retno Fitrian Nastiti; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
This study examines the intellectual trajectory and thematic evolution of Analytical Hierarchy Process (AHP) research in decision-making, with particular emphasis on financial management and risk management contexts, using a bibliometric approach. Quantitative bibliometric analysis was conducted using 483 scientific articles retrieved from the Scopus database, processed through VOSviewer software to map publication trends, author and country collaboration networks, and evolving research themes through co-authorship and co-occurrence analyses. AHP remains a prevalent and methodologically versatile tool in multi-criteria decision-making, with dominant scholarly contributions from China, the United States, and India. Thematically, the literature clusters around risk assessment, multi-criteria decision making, and decision support systems, while emerging trends indicate increasing integration with fuzzy logic and Geographic Information System (GIS) technologies. Practitioners and policymakers in financial management and risk-intensive sectors can draw on AHP-based frameworks to structure complex, multi-criteria evaluations more systematically. This study provides a comprehensive bibliometric mapping of AHP research in management and finance, revealing fragmentation in global collaboration networks and identifying underexplored intersections between AHP and emerging digital technologies as productive directions for future research.